Arbre ou fleur de lys: semblance et senefiance d’une plante miraculeuse dans le miroir de la botanique - Sobczyk, Agata (Studia Romanica Posnaniensia, 2025)
In the well-known exemplum about the simple man who constantly repeated the Ave Maria, a plant plays a central role in the narrative: it is a sign that reveals to witnesses and readers the spiritual value of the main character. In some versions this plant is a lily flower, in others–a tree of unknown species. The article is an attempt to read this motif and its variants through the prism of medieval botanical texts and to find in it some elements of the medieval imagery of the plant.